If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 90 Reorder the terms: -3 + 2x = 90 Solving -3 + 2x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2x = 90 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 90 + 3 2x = 90 + 3 Combine like terms: 90 + 3 = 93 2x = 93 Divide each side by '2'. x = 46.5 Simplifying x = 46.5
| 2(4r-6)=2/3(12r-18) | | -7y+20=6y-6 | | 4x+15-17=16 | | 6x/7=20/14 | | (1-w)(4w+6)=0 | | a=b/c | | 8-4t=6t-22 | | 7x+4=24 | | 15s-8c=5c+48 | | 15X-19+4X+53-8X=2X-43+86+9X+35+-X | | 3m+24=7m | | -1/2m+8=10 | | 68=-2(m+5)+m | | (3x-8)(x+1)=0 | | 3z+24=-7z | | 5=5(x-4)+5-4x | | 4q+2=4 | | 68=-2 | | 1/7(x+2)=4 | | 0.4(0.71+6x)=3.2x | | a/15=b | | let(f)=5x^2-8x+3 | | 8X+59-5X=X-84+242+X | | 8+6+2x=8x | | 4t-2=1 | | x+2=4(4x-3) | | 2x=4-6 | | 3/4(x-16)=-51/4 | | 8p+8=3p-2 | | 6(c-9)=-30 | | 1x+3x+4=4x | | 5X-74+8X=7X+148+5X |